2019
DOI: 10.14744/agri.2019.16779
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy -guided genicular nerves pulsed radiofrequency for chronic knee pain treatment

Abstract: Objectives: The primary objective of this study was to investigate the effects of Pulsed RF application in the genicular nerve on pain and function in patients with osteoarthritis (OA) and its side effects. Methods: This study was conducted between February 2018 and June 2018. Patients who were previously administered diagnostic blocks were evaluated a day later; a drop of at least 50% in numeric pain scores was considered a positive response, and these patients were included in the Pulsed RF neurotomy procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…8 They reported superiority of the use of CFR in the rate of pain reduction more significant than 50% at the assessment after 6 months (CFR 71% vs HA 38%; P < .001), in the WOMAC score at 6 months (48.2 CFR vs 22.6% AH; P < .001), and in the improvement to the perception of global improvement score at 6 months (72 CFR vs 40% HA; P < .01). 8 In 2020, Arıcan et al 9 published a study analyzing 20 patients with knee OA equal to or greater than KellgreneLawrence II submitted to pulsed RF. All analyzed patients were previously submitted to a test block with anesthetic of the genicular nerves, being included in the study only if the pain improved by at least 50% after the test block.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 They reported superiority of the use of CFR in the rate of pain reduction more significant than 50% at the assessment after 6 months (CFR 71% vs HA 38%; P < .001), in the WOMAC score at 6 months (48.2 CFR vs 22.6% AH; P < .001), and in the improvement to the perception of global improvement score at 6 months (72 CFR vs 40% HA; P < .01). 8 In 2020, Arıcan et al 9 published a study analyzing 20 patients with knee OA equal to or greater than KellgreneLawrence II submitted to pulsed RF. All analyzed patients were previously submitted to a test block with anesthetic of the genicular nerves, being included in the study only if the pain improved by at least 50% after the test block.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that pulsed RF of the genicular nerves is a safe and effective technique for patients with chronic OA of the knee. 9 Elawamy et al 10 carried out a prospective randomized study comparing pain improvement, analyzed by the VAS questionnaire, between patients with Kellgrene Lawrence III or IV OA between 2 groups of 100 patients each. Group I underwent pulsed RF in the genicular nerves guided only by ultrasound, and group II underwent intra-articular injection of platelet-rich plasma into the affected knee, also guided by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Encontramos estudios que usan radiofrecuencia pulsada (RFP) a 42°C durante 5 minutos en cada nervio geniculado con buenos resultados, disminuyendo el valor de la escala WOMAC y de la EVA, sin complicaciones o efectos secundarios (37,38). Este tipo de RF tiene la ventaja de no producir una lesión nerviosa que pueda llevar a artropatía neuropática o articulación de Charcot y dolor neuropático secundario; siendo recomendada en la población que no presente una gonartrosis muy avanzada.…”
Section: Discussionunclassified